Developing of Electronic Module on Problem-based Learning (PBL) to Improve Creative Thinking Skills - Dianatur Raviqah; Fatchur Rohman; Sri Rahayu Lestari (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2023)
Creative thinking skills can be empowered to students during the learning process using appropriate learning materials. The study aimed to develop electronic module on problem-based learning that is valid, practical and effective to improve students' creative thinking skills. This development follows the model of Lee & Owens (Assessment/ analysis; Design; Development; Implementation; and Evaluation). The validity was determined based on expert assessment (media, material, educational practitioners) and practicality was evaluated based on field practitioners and students' responses which were analyzed descriptive quantitative percentages. Meanwhile, the effectiveness data were collected through open questions to assess the improve in creative thinking skills based on the rubric of creative thinking skills and analyzed using the N-gain score. The results showed that the developed electronic module on problem-based learning was declared as very valid (98.6%), very practical based on practitioners' responses (93.55%) students' responses (95.92%), and effective for improving creative thinking skills (0,35). Hence, it can be concluded that electronic module on problem-based learning can be used to improve students' creative thinking skills.